Solve for y 6-y=26

Math
6-y=26
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
-y=26-6
Subtract 6 from 26.
-y=20
-y=20
Multiply each term in -y=20 by -1
Tap for more steps…
Multiply each term in -y=20 by -1.
(-y)⋅-1=20⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=20⋅-1
Multiply y by 1.
y=20⋅-1
y=20⋅-1
Multiply 20 by -1.
y=-20
y=-20
Solve for y 6-y=26

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top